(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda represents a very effective alternative system of medicine with its effective therapies like Yoga, Mud Therapy, Ahara Chikitsa and many others. Among which Marma Chikitsa is developing and gaining importance. It is a precise art of touching an individual in exactly the right place at a critical moment in time, for the purpose of healing and bringing flawless results in a lot of disorders that are creating hindrances in healthy life of an individual. One of such lifestyle relayed disorders is diabetes mellitus which if not controlled later on leads to neuropathy, nephropathy and retinopathy. Today diabetic retinopathy has become one of the leading causes of blindness worldwide. So, attracting researchers to find out ways to control its progression and treating it well. Treatment involves laser, photocoagulation, viterectomy etc. They are effective for short time, but on the other side, having high reoccurrence rates and discomfort to an individual. Here hidden treasures of Ayurveda can be explored to help mankind. One of such hidden asset is Marma Chikitsa. Marma Chikitsa involves pressing Marma points which causes release of blockage of energy, removes excess Ama, facilitates easy flow of energy, nourishes the tissues, produces endorphins and cortisol like hormones in-turn induces calm shut off FFF response and improves blood circulation. All these activities cause better functioning of that particular area. Some of the Marma points stimulation that are related to eyes and some that helps in better metabolism like Apanga, Avarta, Sthapni, Vidhura, Kurcha, Kurchshira, Indravasti and Nabhi can play a good role in checking progression of retinopathy with pathya Ahara, healthy lifestyle, exercises and proper medication. Marma Chikitsa can be a safe, convenient, cost-effective adjuvant remedy in dealing diabetic retinopathy.